Long-term outcome of nonmyeloablative allogeneic transplantation in patients with high-risk multiple myeloma - Gerull, Sabine; Görner, Martin; Benner, Axel; Hegenbart, Ute; Klein, Ulrike; Schäfer, Hansjörg; Goldschmidt, Hartmut; Ho, Anthony Dick (Bone marrow transplantation, 2005)
Conventional treatment or autologous transplantation has not been able to achieve long-term remission in patients with multiple myeloma (MM). Nonmyeloablative allogeneic transplantation might offer an option for cure without the high mortality associated with conventional conditioning. Here we present a retrospective analysis of patients with high-risk MM treated with nonmyeloablative allogeneic transplantation. In all, 52 patients with relapsed MM or high-risk features at diagnosis received 2 Gy TBI alone (n=3) or with fludarabine (n=49) as conditioning. Patients were heavily pretreated with a median of eight cycles of conventional chemotherapy and one or more autologous transplants for all but one patient. Regimen-related toxicity was low. Acute graft-versus-host disease II-IV occurred in 37% of patients, and 70% experienced chronic graft-versus-host disease (cGvHD). Median follow-up was 567 days, and transplant-related mortality was 17% in total. Estimated progression-free and overall survival at 18 months was 29.4 and 41.1%, respectively. Patients with cGvHD had a significantly higher progression-free survival, as did patients with up to eight cycles of pretreatment chemotherapy vs those with nine or more. In this highly pretreated patient group, disease control was unsatisfactory and our results suggest that a potential strategy might be to perform allogeneic transplant earlier in the course of the disease.
Gesehen am 15.02.2022